Coproduction of protease and amylase by thermophilic Bacillus sp. BBXS-2 using open solid-state fermentation of lignocellulosic biomass. (October 2016) - Qureshi, Abdul Sattar; Khushk, Imrana; Ali, Chaudhry Haider; Chisti, Yusuf; Ahmad, Ayyaz; Majeed, Hamid
Abstract: A nonsterile open solid-state fermentation process was used to coproduce bacterial protease and amylase for possible use in detergents. The thermophilic bacterium Bacillus sp. BBXS-2 was used to produce the enzymes. Of the several substrates (i.e. sugarcane bagasse, wheat straw, rice straw, and rice husk) evaluated for this fermentation, wheat straw proved to be the best. A comparison of monoseptic and nonsterile open fermentations showed no significant difference in enzyme production. The thermophilic and alkalophilic conditions used helped in minimizing contamination. Under optimal nonsterile conditions the concentrations of enzymes after a 5-d fermentation (45 °C, initial pH of 8.5) using wheat straw as substrate were ∼12, 200 U/g dry matter for protease and 6, 900 U/g dry matter for amylase. Supplementation of commercial laundry detergents with the crude enzymes produced in this work demonstrated up to 2.5-fold enhancement in their ability to remove starchy stains. Nonsterile open solid-state fermentations on cheap agroindustrial substrates provide new opportunities for low-cost production of industrial enzymes for applications such as in laundry detergents. Highlights: Untreated lignocellulosic biomass is fermented to produce bacterial enzymes. An open (nonaseptic) solid-state fermentation is used to minimize costs. Thermophilic/alkalophilic fermentation conditions could control contamination. Much higher titers of enzymes were produced compared to the literature. Enzymes added to laundry detergents improved stain removal by ∼2.5-fold.